Fracture resistance of monolithic zirconia molar crowns with reduced thickness. (November 2015) - Nakamura, Keisuke; Harada, Akio; Inagaki, Ryoichi; Kanno, Taro; Niwano, Yoshimi; Milleding, Percy; Örtengren, Ulf
Abstract: Objectives. The purpose of the present study was to analyze the relationship between fracture load of monolithic zirconia crowns and axial/occlusal thickness and to evaluate the fracture resistance of monolithic zirconia crowns with reduced thickness in comparison with that of monolithic lithium disilicate crowns with regular thickness. Materials and methods. Monolithic zirconia crowns (Lava Plus Zirconia, 3M/ESPE) with specified axial/occlusal thicknesses and lithium disilicate crowns (IPS e.max press, Ivoclar/Vivadent) with regular thickness were fabricated using a dental CAD/CAM system and a press technique, respectively. The crowns cemented onto dies were loaded until fracture. Based on measurements of the crown thickness made by micro-CT and the fracture load, multiple regression analysis was performed. Results. It was revealed that the occlusal thickness significantly affected the fracture load ( p < 0.01), but the axial thickness did not ( p = 0.2828). Although the reduction of the occlusal thickness decreased the fracture resistance of the monolithic zirconia crowns, the fracture load of the zirconia crowns with the occlusal thickness of 0.5 mm (5558 ± 522 N) was significantly higher than that of lithium disilicate crowns with an occlusal thickness of 1.5 mm (3147 ± 409 N). Conclusion. Within the limitations of the present study, it is suggested that monolithic zirconia crown with chamfer width of 0.5 mm and occlusal thickness of 0.5 mm can be used in the molar region in terms of fracture resistance.